Optimization of fluorine content in TFA-MOD precursor solutions for YBCO film growth. (16th November 2015) - Jin, L H; Li, C S; Feng, J Q; Yu, Z M; Wang, Y; Lei, L; Zhao, G Y; Sulpice, A; Zhang, P X
Abstract: Several low fluorine solutions containing different contents of fluorine were prepared by a chemical process. The fluorine contents in these solutions with respect to the conventional all-trifluoroacetate solution were calculated as 0%, 7.7%, 15.4%, 23.1%, 30.8%, 38.5% and 53.8%. YBa2 Cu3 O7− x (YBCO) films were deposited on LaAlO3 and CeO2 /MgO/Al2 O3 /Hastelloy substrates using these low fluorine solutions. The phase formation, texture and microstructure of the YBCO films were characterized by x-ray diffraction and scanning electron microscopy. The decomposition mechanism of the low fluorine solution was also discussed. The results indicate that the ratio of F/Ba and the carbon content in decomposed powders could be controlled by adjusting the fluorine content in the precursor solutions. Fluorine had a great influence on the phase transformation, nucleation and growth of YBCO film during the crystallization process. The optimization of fluorine content was in the range of 15.4%–23.1%, which contributed to the good texture, homogeneous microstructure and high J c value of the YBCO crystallized films.